The Prevalence of Blood Groups in Domestic Cats in the Saskatoon and Calgary Areas of Saskatchewan and Alberta, Canada - McDermott, Fergal M.; Maloney, Stephanie; McMillan, Chantal; Snead, Elisabeth (Frontiers in Veterinary Science, 2020)
The purpose of this study was to evaluate blood types of domestic cats in two cities in Western Canada (Saskatoon, Saskatchewan and Calgary, Alberta), as well as to determine the risk of mismatched transfusion and neonatal isoerythrolysis. Several cat studies around the world have shown variability in the prevalence of blood types in domestic and pedigree cats. Canadian data based on feline blood types is based out of Montreal. In this study the cohort of cats revealed a higher than anticipated prevalence; of 5% type B and 0.6% AB blood types. In our study, blood typing was performed in 400 domestic cats; 200 in Saskatoon and 200 in Calgary. Blood typing was performed using the gel tube method and the risk of transfusion mismatch (MT) was estimated by adding the risk of a major transfusion reaction and the risk of a minor transfusion reaction. The risk of neonatal isoerythrolysis (NI) was estimated according to the equation (p2)(q2) + 2pq(q2), with q being the b allele frequency and p = 1 – q. There was an identical frequency for feline blood types in both Saskatoon and Calgary cats, with 96% type A, 4% type B, and 0% AB. Based on these percentages, the risks of MT and NI in domestic cats were 7.6 and 4 % respectively. The frequency of type B cats in the population was similar to that in the previous Canadian study. These results demonstrate regional differences in prevalence of type B blood in domestic shorthairs across the world and serve to reinforce recommendations to blood type prior to transfusion or mating.